Characterization of the Biocidal Spectrum of Extracellular Filtrates of Microcystis aeruginosa - Jaiswal, Pranita (Springer-Verlag, 2011)
The effect of dichloromethane (DCM) and ethyl acetate (EA) extract of a cyanobacterium, Microcystis aeruginosa was evaluated against unicellular cyanobacteria and the phytopathogenic fungus Rhizoctonia solani. Fractionation of the filtrate showed the presence of five spots of different Rf values on silica gel coated plates indicating the presence of a number of compounds in the extract. A marked reduction in growth (52%) of the fungus was recorded on the plates supplemented with cyanobacterial extract, indicating the involvement of anti-fungal metabolite(s). The extract did not show any negative influence on seed germination and growth of seedlings of wheat, rice and mung, emphasizing the suitability of the compound for use in agriculture.